Calcinosis cutis in systemic sclerosis: a conundrum - Mourad, Youssef W.; Loius, Martine A. (International Surgery Journal, 2021)
Calcinosis cutis (CC) is an autoimmune disorder that presents with a wide range of systemic manifestations. Respiratory and gastrointestinal tracts along with skin are affected. Skin manifestations can progress to significant deformities, causing discomfort to patients severely affecting quality of life. Management of patients with Scleroderma requires a multidisciplinary approach in order to attain the best possible outcomes. Wound care is not yet standardized and multiple approaches exist with varying degrees of success. Surgical approaches vary based on anatomical location along with the depth and area of the wound. It is imperative to provide continuity of care with this patient population. If there is not adequate communication with regards to expectations, the disease burden may progress and ultimately prolong patient treatment. We presented the case of a 65 year old female with scleroderma that is followed within our wound care clinic for long term care of cutaneous lesions. Wound healing varied throughout the duration of treatment with moderate success seen with the use of wound vac therapy.